(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
This paper provides new data on strontium isotope stratigraphy applied to the Miocene heterozoan shelfal carbonates of the S. Marino Fm. (Marecchia Valley, northern Apennines). Sr isotopic analyses were carried out on oyster shells, bryozoans and bulk-rocks from the lower-middle carbonate portion of the section. In the upper part of the succession that shows evidence of detrital influx,87Sr/86Sr analyses were performed on foraminifera tests, separating planktonic and benthic forms. Results were compared with calcareous nannofossil biostratigraphic data from the same levels, in order to test the reliability of Sr dating in mixed carbonate-siliciclastic sediments. Mean ages obtained from oysters range between 16.9 Ma and 16.3 Ma. Very similar results are obtained using bryozoans (16.5 Ma to 16.1 Ma) and bulk-rocks (16.8 Ma to 16.2 Ma). These results allow to better constrain the age of the massive carbonate shelf, referable to the upper Burdigalian. In the upper carbonate-siliciclastic portion of the shelf, numerical ages obtained from planktonic and benthic foraminifera are in good agreement with nannofossil biozones (mean ages respectively around 15.3 Ma and 14.5 Ma) although they display wide confidence intervals. These wide age uncertainties depend on the slow rate of change of marine 87Sr/86Sr through time that characterizes the interval between 15 and 13.5 Ma.